Concentration versus streamflow trends of major ions and tritium in headwater streams as indicators of changing water stores. Issue 2 (1st December 2019) - Cartwright, Ian; Morgenstern, Uwe; Hofmann, Harald
Abstract: Documenting the processes that control the variations in stream geochemistry at different streamflows is important for being able to use chemical tracers to understand catchment functioning. The concentrations of most solutes, including reactive cations (e.g., Na, Ca, K, and Mg) and anions that are primarily derived from precipitation (Cl and Br), in five headwater streams from southeast Australia vary little with streamflow and are close to being chemostatic. By contrast, NO3 and SO4 concentrations are higher at high streamflows. There is also a systematic increase of 3 H activities from as low as 1.1 to as high as 2.6 TU with increasing streamflow. The changes in geochemistry cannot be explained solely by increased mineral dissolution at high streamflows or enhanced baseflow driven by hydraulic loading. They are best explained by an increased baseflow input augmented by water mobilized from shallower stores as the catchments wet up. The mean transit times of the water sustaining streamflow varies from 35 to 70 years at low streamflows to <7 years at high streamflows. The use of a range of geochemical tracers, including radioactive isotopes, allows the different possible causes of chemostatic behaviour to be assessed and improves our understanding of catchment functioning. Abstract : Concentrations of most major ions in headwater streams from southeast Australia vary little with streamflow. Analysis of geochemical processes coupled with mean transit times estimated using tritium imply that mobilization of shallow stores of water augment baseflow as the catchments wet up. This information is vital to understanding the functioning of and managing these catchments.